Pengelolaan Piutang Dalam Penyelesaian Kredit Macet Pada Perumda BPR Bank Kota Bogor - Fadillah, Muhammad; Andrianto, Toni; Muanas, Muanas (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Implementation of Receivable Management _______453 Submitted FEBRUARY 2024 Accepted OCTOBER 2024 JABKES Jurnal Aplikasi Bisnis Kesatuan Vol. 4 No. 3, 2024 page. 453-464 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v4i3.1934 Accounts receivable management is crucial for companies, especially those selling products on credit. Effective management of receivables ensures that credit returns are handled efficiently, leading to increased company revenue. In this final project, it is noted that receivables management at Perumda BPR Bank Kota Bogor is carried out both manually and through a system. Despite this, problematic and non-performing loans still occur. These problematic and non-performing loans arise due to internal factors within the bank, such as errors in credit analysis and inadequate data verification. Additionally, external factors from the debtors include a decrease in the debtor's payment ability, business losses, reassignment or termination of the debtor, and the misuse of credit by the debtor for purposes other than intended. The resolution of problematic and non-performing loans has been addressed through rescheduling, reconditioning, restructuring, collateral takeovers, and write-offs. Perumda BPR Bank Kota Bogor also undertakes measures to minimize the occurrence of problematic and non-performing loans in the future by conducting detailed and accurate credit analysis, regular monitoring, and maintaining good relationships with debtors. Keywords: Receivables Management, Causes of Non-Performing Loans, Resolution of Non-Performing Loans